The Effect of Post-Treatment N -Acetylcysteine in LPS-Induced Acute Lung Injury of Rats - Choi, Jae Sung; Lee, Ho Sung; Seo, Ki Hyun; Kim, Yong Hoon; Uh, Soo Taek; Park, Choon Sik; Oh, Mee Hye; Lee, Sang Han; Kim, Young Tong (Tuberculosis and respiratory diseases, 2012)
Oxidation plays an important role in acute lung injury. This study was conducted in order to elucidate the effect of repetitive post-treatment of N-acetylcysteine (NAC) in lipopolysaccaride (LPS)-induced acute lung injury (ALI) of rats. Six-week-old male Sprague-Dawley rats were divided into 4 groups. LPS (Escherichia coli 5 mg/kg) was administered intravenously via the tail vein. NAC (20 mg/kg) was injected intraperitoneally 3, 6, and 12 hours after LPS injection. Broncho-alveolar lavage fluid (BALF) and lung tissues were obtained to evaluate the ALI at 24 hours after LPS injection. The concentration of tumor necrosis factor α (TNF-α) and interleukin 1β (IL-1β) were measured in BALF. Nuclear factor κB (NF-κB), lipid peroxidation (LPO), and myeloperoxidase (MPO) were measured using lung tissues. Micro-computed tomography (micro-CT) images were examined in each group at 72 hours apart from the main experiments in order to observe the delayed effects of NAC. TNF-α and IL-1β concentration in BALF were not different between LPS and NAC treatment groups. The concentration of LPO in NAC treatment group was significantly lower than that of LPS group (5.5±2.8 nmol/mL vs. 16.5±1.6 nmol/mL) (p=0.001). The activity of MPO in NAC treatment group was significantly lower than that of LPS group (6.4±1.8 unit/g vs. 11.2±6.3 unit/g, tissue) (p<0.048). The concentration of NF-κB in NAC treatment group was significantly lower than that of LPS group (0.3±0.1 ng/µL vs. 0.4±0.2 ng/µL) (p=0.0001). Micro-CT showed less extent of lung injury in NAC treatment than LPS group. After induction of ALI with lipopolysaccharide, the therapeutic administration of NAC partially attenuated the extent of ALI through the inhibition of NF-κB activation.